Chronic Hepatitis C with Cyanosis - Mahmood Alawainati; Jawad Khamis; Muneer Abdulla; Saeed Alsaeed (Case Reports in Hepatology)
Background. There are multiple aetiologies for dyspnea in patients with liver disease, including pneumonia, pulmonary embolism, hepatic hydrothorax, portopulmonary syndrome, and hepatopulmonary syndrome. The aim of this paper is to emphasize the importance of early diagnosis and management of hepatopulmonary syndrome. Case Presentation. We report a case of a 65-year-old male who was known to have chronic hepatitis C presented with one-year history of shortness of breath and cyanosis. The initial impression of pulmonary embolism was excluded by comprehensive diagnostic investigations. The correlation between the clinical picture and investigations raised the possibility of hepatopulmonary syndrome which was confirmed by contrast-enhanced transthoracic echocardiography. Conclusions. High suspicion is required to diagnose hepatopulmonary syndrome in patients with liver disease and hypoxemia. Screening for this complication is appropriate in liver transplant candidates, and diagnosed patients should be evaluated extensively for liver transplant.